HUBUNGAN DEBT TO EQUITY RATIO (DER) DAN NET PROFIT MARGIN (NPM) DENGAN HARGA SAHAM PADA PT MAYORA INDAH Tbk PERIODE 2013 - 2023 - Alifya; Elfahmi, Ryan (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the relationship between Debt to Equity Ratio and Net Profit Margin on Share Price at PT Mayora Indah Tbk for the period 2013 - 2023. The method used is quantitative. The population used in this study were all financial statements of PT Mayora Indah, where the sample in the study was the financial statements for the period 2013-2023. The data analysis used is Descriptive Statistical Test, Classical Assumption Test, Model Feasibility Test, Multiple Linear Regression Test, and Pearson Bivariate Correlation Hypothesis Test. The results of hypothesis research show the Sig. (2-tailed) between Deb to Equity Ratio and Stock Price is 0.001 <0.05. This shows that there is a relationship between Deb to Equity Ratio and Stock Price. Net Profit Margin with Share Price shows a Sig value. (2-tailed) of 0.267> 0.05. This shows that there is no relationship between Net Profit Margin and Stock Price.